Theory-Practice Relationship, Between the Initial Training Field and the Professional Practice Scenario - Sánchez-Sánchez, Gerardo Ignacio (2016)
This article, developed at the regional campus of a university, located 200 miles south from Santiago de Chile, shows how 185 students of preschool, elementary and middle education, experience and perceive the relationship theory-practice from their insertion in the school environment. The mixed approach adopted relies on an opinion questionnaire and a semi-structured interview administered in the tutoring spaces. The results show that 39% of the teaching students believe that theory and practice are opposite realities, while 31% say that the theory depends on practice. In that scenario, the initial teaching training faces the challenge to create spaces and devices that allow the teaching student to get familiar with a few sets of flexible and changing rules to understand the specificity of the teaching process, from a proper theory-practice relationship.